RANCANG BANGUN SISTEM PEMANTAU SUHU BEARING MOTOR UNTUK POMPA SIRKULASI AIR BERBASIS IOT - Artana, I.G.W.; Ariastina, W.G.; Kumara, I.N.S. (Jurnal SPEKTRUM, 2022)
The importance of monitoring the temperature of the motor bearing on the water circulation pump on a regular basis to prevent pump operation failures due to bearing. The operator monitors the temperature bearing manually using a Flir measuring instrument with potential hazards in the work area namely slipping, falling and electrocution. On this basis, IoT based bearing monitoring system for circulation water pump in real time is very necessary.The design of this prototype uses hardware such as ESP32 microcontroller and MLX90614-BCC sensor, while the software used are blynk and google spreadsheet. The MLX90614-BCC sensor calibration uses a linear regression method to adjust the sensor value to the Flir TG167 so as to minimize deviations in temperature readings.The results of this prototype are able to read temperature bearing well which are integrated with the blynk on smartphones by displaying temperature values in the form of numbers and graphs and also equipped with a notification. The prototype that was built had an average measurement deviation of 0.32% on the DE sensor and 0.3% on the NDE sensor. Storage of temperature data on google spreadsheet with the amount of data that can be stored as much as 1,666,666 data. The conclusion of the research is that it has succeeded in designing and manufacturing a prototype IoT based bearing monitoring system for circulation water pump. Testing the performance of the prototype can work well. The results of the prototype test on bearing for the water circulation pump showed that DE and NDE bearing temperatures were still below 55 °C and there was no notification on the smartphone which indicates the motor bearing is still in normal condition.